LEGAL SUCCESSION OF LEGAL ENTITIES IN LAND RELATIONS: THEORETICAL AND PRACTICAL ASPECTS - Armash, Nadiia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
The purpose of the article is to determine the specifics of the application of current legislation when a legal entity is terminated in the form of liquidation or reorganization and, accordingly, to clarify the issue of legal succession of a legal entity in land relations. Research methods: research during the writing of the article was conducted using general scientific methods of analysis and synthesis to clarify the content of the phenomenon of legal succession in economic and legal relations and to develop the terminological foundations of the chosen topic. Results: the conclusions made as a result of the generalization of theoretical provisions, legislation and judicial practice are the basis for improving the work of business entities, ensuring predictability in the activities of these entities, including in the conditions of reorganization. Discussion: sustainable practice of applying the provisions of the legislation in the recognition of legal succession of legal entities in land relations. Transformations in the conditions of business management make adjustments to the activities of business entities themselves, forcing them to optimize their structure, including through reorganization. In this context, clear and stable legislation and the practice of its application are gaining weight for a more predictable legal field. As rightly noted in the literature, «The complication of the object of management – the economy of Ukraine, which is in a deplorable state, determines the need to raise the quality, efficiency of legislative activity, law-making activity to a higher level, and to solve the existing problems of law-making». Actually, the question of legal succession periodically arises during the activity of many business entities, or in the case of their own reorganization, or if they become the legal successors of other reorganized enterprises. In addition to a certain amount of property and non-property rights, the obligations of the predecessors also pass to the successors, so it is important to clarify the scope and possibilities of implementing the powers they received. Summarizing the research on the legal succession of legal entities in land matters, it should be pointed out the unity of legislation and practice in the matter of recognizing the transfer of rights and obligations of the legal entity – the predecessor to the legal entity of the legal successor. Most of all, the legislator does not contain restrictions on legal succession, but the provisions of the Law of Ukraine «On Leasing of State and Communal Property» do not allow persons who have anti-corruption or sanction restrictions to obtain the right to lease state or communal property.